Enhancing Supply Chain Management Performance Through E-CRM Implementation - Hail, Chifae El; Koraichi, Mustapha El (ExcelingTech, 2024)
This paper aims to explore practical ways in which Small and Medium Enterprises (SMEs), considering their limited resources and capabilities, can harness the benefits of E-Customer Relationship Management (E-CRM) to optimize and improve their Supply Chain Management (SCM) performance. An in- depth case study within a family SME demonstrates how E-CRM contributes to improving key elements of supply chain performance, including demand forecasting, inventory management, delivery routes, and returns management. The measured impact on customer satisfaction, delivery punctuality, order processing time, demand forecast accuracy, and inventory costs reaffirms the value of E-CRM in improving overall SCM performance. The contributions of the study include integrating E-CRM and SCM concepts, addressing implementation challenges, and offering valuable guidance for SMEs aiming to improve logistical performance through E-CRM.